2013
DOI: 10.1088/0957-4484/24/50/505705
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-phase synthesis, growth mechanism and thickness-independent elastic modulus of single-crystal tungsten nanobelts

Abstract: Single-crystal tungsten nanobelts with thicknesses from tens to hundreds of nanometers, widths of several micrometers and lengths of tens of micrometers were synthesized using chemical vapor deposition. Surface energy minimization was believed to have played a crucial role in the growth of the synthesized nanobelts enclosed by the low-energy {110} crystal planes of body-centered-cubic structure. The anisotropic growth of the crystallographically equivalent {110} crystal planes could be attributable to the asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Owing to its simplicity and efficiency in operation, the resonant vibration testing was widely used to determine the elastic modulus of NWs including Si,154, 166 Ge,167 Co,168 W,161, 169 SiC,170 GaN,99, 171 Ag 2 Ga,154 BN,172 ZnO,149, 165, 173, 174 WO 3 ,175 In 2 O 3 ,168 Sb 2 O 3 ,176 Al 2 O 3 ,164 amorphous SiO 2 ,177 metallic glasses 153. In particular, the use of SLDV not only significantly increases the detection resolution of a NW specimen's vibrational spectra, but also eliminates the issues relating to clamping and dimensional non‐uniformity 154, 161, 164.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its simplicity and efficiency in operation, the resonant vibration testing was widely used to determine the elastic modulus of NWs including Si,154, 166 Ge,167 Co,168 W,161, 169 SiC,170 GaN,99, 171 Ag 2 Ga,154 BN,172 ZnO,149, 165, 173, 174 WO 3 ,175 In 2 O 3 ,168 Sb 2 O 3 ,176 Al 2 O 3 ,164 amorphous SiO 2 ,177 metallic glasses 153. In particular, the use of SLDV not only significantly increases the detection resolution of a NW specimen's vibrational spectra, but also eliminates the issues relating to clamping and dimensional non‐uniformity 154, 161, 164.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…In particular, the use of SLDV not only significantly increases the detection resolution of a NW specimen's vibrational spectra, but also eliminates the issues relating to clamping and dimensional non‐uniformity 154, 161, 164. Moreover, the resonance‐based testing can be performed without contact of a NW, thus not necessitating the consideration of temperature effects on force and displacement measurements.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…[1][2][3][4] In most of the NW/substrate based devices, the static friction force is the one that holds the NW in position and in shape, 5,6 while the kinetic friction force will influence its movement. 7 Although friction has been brought into the field of physics for over centuries, the underlying mechanism of friction at nanoscale is not well understood yet as those laws that govern the friction at macroscale are not valid.…”
Section: Introductionmentioning
confidence: 99%
“…The drawback of this material in bulk form is its high brittleness or low ductility, which has somehow hindered its widespread applications. In the past two or three decades, researchers have shown that some materials in the form of nanostructures exhibited novel properties in comparison to their bulk counterparts . SiC nanorods was found being fractured at an extremely high strain of approximately 10%, which is close to the theoretical prediction, in a bending test performed on an atomic force microscope and SiC nanowires could experience a strain up to 4.5% prior to brittle fracture during the tensile test performed in an scanning electron microscope (SEM).…”
mentioning
confidence: 99%